Prevalence of Parasitic Contamination in Salad Vegetables Collected from Supermarkets and Street Vendors in Amman and Baqa’a – Jordan - Yazan Ismail (Polish Journal of Microbiology, 2016)
One of the main ways in transmitting parasites to humans is through consuming contaminated raw vegetables. The aim of this study was to evaluate the prevalence of parasitological contamination (helminthes eggs, Giardia and Entamoeba histolytica cysts) of salad vegetables sold at supermarkets and street vendors in Amman and Baqa’a – Jordan. A total of 133 samples of salad vegetables were collected and examined for the prevalence of parasites. It was found that 29% of the samples were contaminated with different parasites. Of the 30 lettuce, 33 tomato, 42 parsley and 28 cucumber samples examined the prevalence of Ascaris spp. eggs was 43%, 15%, 21% and 4%; Toxocara spp. eggs was 30%, 0%, 0% and 4%; Giardia spp. cysts was 23%, 6%, 0% and 0%; Taenia/Echinococcus eggs was 20%, 0%, 5% and 0%; Fasciola hepatica eggs was 13%, 3%, 2% and 0%; and E. histolytica cysts was 10%, 6%, 0% and 0%, respectively. There was no significant difference in the prevalence of parasite in salad vegetables either between supermarkets and street vendors, or between Amman and Baqa’a, Ascaris spp. was found to be the highest prevalent parasite in salad vegetables from supermarkets and street vendors and from Amman and Baqa’a. Our results pointed out that, the parasitic contamination of salad vegetables found in our study might be caused by irrigating crops with faecal contaminated water. We concluded that salad vegetables sold in Amman and Baqa’a may cause a health risk to consumers.